2010
DOI: 10.1136/bcr.08.2009.2208
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal lichen planus: preservation of sexual function in severe disease

Abstract: Lichen planus is a multisystem disease. Often genital involvement is missed or misdiagnosed. It can be rapidly progressive with high patient morbidity. This case highlights the importance of a multidisciplinary approach and the effectiveness of combined surgical and medical treatment with close patient follow-up and support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…In this study, urogenital abnormalities associated with LP, were represented by bacterial/fungal infections, urethritis, pyelonephritis, cystitis and problems in urine evacuation. Some studies have shown the association between vaginal LP and squamous cell carcinoma, human papilloma virus (HPV) infection or dysuria [6,7].…”
Section: Leukocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, urogenital abnormalities associated with LP, were represented by bacterial/fungal infections, urethritis, pyelonephritis, cystitis and problems in urine evacuation. Some studies have shown the association between vaginal LP and squamous cell carcinoma, human papilloma virus (HPV) infection or dysuria [6,7].…”
Section: Leukocytesmentioning
confidence: 99%
“…Lichen planus (LP) is a complex immunologically mediated disease, which affects the skin and mucous membranes, being an important concern for medical research [1][2][3][4][5][6][7]. The global prevalence of LP varies between 0.22 and 5% [8].…”
mentioning
confidence: 99%
“…Hypertrophic variant is the rarest among vulval LP and when present usually mimics squamous cell carcinoma. 4 The main differential diagnosis to be considered in this setting is verrucous carcinoma of the vulva, a variant of squamous cell carcinoma. They are characterised by asymptomatic, slow-growing exophytic lesions on the vulva, which may be locally destructive.…”
Section: Discussionmentioning
confidence: 99%
“…The disease occurs mainly in the oral mucosa, but it can also develop in the female vagina (Machin et al 2010 ), where it is often missed or misdiagnosed. The authors reported that the vaginal manifestation can progress rapidly, increasing morbidity and affecting sexual function; if left untreated, it can produce adhesions that completely occlude the vagina, requiring surgery.…”
Section: On the Diseasementioning
confidence: 99%